If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -1y = -1 + -2y Combine like terms: 2y + -1y = 1y 1y = -1 + -2y Solving 1y = -1 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. 1y + 2y = -1 + -2y + 2y Combine like terms: 1y + 2y = 3y 3y = -1 + -2y + 2y Combine like terms: -2y + 2y = 0 3y = -1 + 0 3y = -1 Divide each side by '3'. y = -0.3333333333 Simplifying y = -0.3333333333
| 2k^2-8k= | | 6x^2-30x+8=0 | | 5(2y+7)=3y-1 | | z^2-15z=0 | | 7x-6=x-2 | | 3x+16=42 | | 3p-1=-2 | | 3(2x-5)+7x=3x+35 | | 3/4x-2 | | -5x^2+4x=91 | | 1.2c+2.6c=4.55 | | 2/7(x-5/4)=-1/7 | | -3(4x+5)=-63 | | 5(x-9)=2(x+7) | | T-6=10 | | H=-16t^2+38t+104 | | 10x=4-(-16) | | 2x-4n=7-n | | ax+bx-9=-10 | | 18xsquared-6x-8= | | 275000.00x=13000.00+25000.00x | | 4/7x=26 | | 2(5x)+3x=7 | | 3(x+8)=x+12 | | 2x-4n=18-n | | -3y-5(y+4)=4 | | 7/3x-5 | | 2(9-2x)=26 | | 24x+12=63 | | 143=11S+11 | | B=17-14 | | 12-9x=4-5x |